Fatty acid concentrations and compound-specific carbon stable isotopes of sediments, filtered particulate organic carbon, and crab tissue from the hydrothermal vent system off Kueishantao, Taiwan - Maak, Joely Marie; Lin, Yu-Shih; Schefuß, Enno; Aepfler, Rebecca F; Liu, Li-Lian; Elvert, Marcus; Bühring, Solveig I (PANGAEA, 2025)
This dataset comprises fatty acid concentrations and compound-specific carbon stable isotopes of short-chain fatty acids (bacterial biomarkers) found in samples from the shallow-water hydrothermal vents off Kueishantao. The samples investigated here include surface sediments, sections from short sediment cores, filtered vent fluids, filtered particulate organic carbon (POC), and material from the vent endemic crab (𝘟𝘦𝘯𝘰𝘨𝘳𝘢𝘱𝘴𝘶𝘴 𝘵𝘦𝘴𝘵𝘶𝘥𝘪𝘯𝘢𝘵𝘶𝘴). The surface sediments close to the individual vent systems (1 m and 20 m distance) and a background site (M4) were taken in April 2014 during the OR2-2024 cruise. Short sediment cores of 20 cm directly at the individual vents, vent fluids, material from 𝘟. 𝘵𝘦𝘴𝘵𝘶𝘥𝘪𝘯𝘢𝘵𝘶𝘴, and filtered POC in close distance to the vents were retrieved during the OR2-2095 cruise (17-18 May 2015) and one cruise that utilized fishing boats (25-28 May 2015). For more details on the sampling locations see published data in Lin et al. (2019) (doi:10.1016/j.marchem.2019.02.002). The reported δ13C values of the fatty acids were corrected for methylation. Next to the concentrations and compound-specific stable carbon isotopes of fatty acids, we also report the percentage of Campylobacteria (chemoautotrophs using the reductive tricarboxylic acid cycle (rTCA) for carbon uptake) in the individual samples. This percentage was calculated from a rTCA endmember (-7.2‰, most 13C enriched fatty acid) and a Calvin-Benson-Bassham endmember (-27‰, mean in background fatty acids) from fatty acids known to be produced by sulfur oxidizers (C16:1ω7c, C16:1ω7t, n C16:0, C18:1ω9, C18:1ω7c, and C18:1ω7t).
Keywords: Carbon isotopes; chemoautotrophy; fatty acids; Kueishantao; reductive tricarboxylic acid cycle; shallow-water hydrothermal vents; trophic transfer